In Vitro Evaluation of the Dual‐Diffuser Design for a Reversible Rotary Intra‐Aortic Ventricular Assist Device. Issue 9 (30th June 2016) - Wang, Yaxin; Smith, P. Alex; Timms, Daniel L.; Hsu, Po‐Lin; McMahon, Richard A.
Abstract: The intra‐aortic ventricular assist device (IntraVAD) is a miniature intra‐aortic axial‐flow ventricular assist device (VAD) that works in series with the left ventricle (LV) to assist the compromised heart. Previous in vitro results have shown that the IntraVAD can successfully increase coronary perfusion and offload ventricular volume by operating in reverse‐rotation control (RRc) mode. The RRc mode includes forward rotation in systole and reverse rotation (RR) in diastole. It is necessary to derive a new diffuser design that can be used for the bi‐directional rotation of the IntraVAD. In this work, a dual‐diffuser set (DDS) was proposed to replace the conventional inducer and diffuser upstream and downstream of the pump. The DDS comprised two diffusers, located on both sides of the impeller, omitting the conventional inducer and diffuser. Different configurations of the DDS were designed and manufactured with various combinations of curved and straight blades. All configurations were initially tested in continuous flow, then in a pulsatile mock circulatory loop. A weighted normalized scalar (WNS) was proposed to comprehensively evaluate the hemodynamic effect of the DDS with different configurations. The results show that the maximum of WNS occurred when the upstream diffuser had equal numbers of curved and straight blades and the downstream diffuser had only curved blades. This indicates such a dual‐diffuser design for the IntraVAD can give an optimal cardiac assistance potentially improving ventricular contractility, thereby restoring heart function.